Evaluating "Ing Ngarso, Ing Madyo, Tut Wuri" in English Teaching: Success or failure? - Sirwan, Lalu Banu; Ghozali, Imam (Journal of English Language and Pedagogy, 2023)
This research aimed to (1) ascertain the context, (2) describe the quality inputs, (3) investigate the process, and (4) examine the product. This research is evaluation research employing the CIPP model by Stufflebeam (2007). The data were collected through classroom observation, interviews, and documentation. The result shows that the context contributes to the product because the vision and mission indicated how the implementation of the teaching of Tamansiswa especially 2 Ings and Tut implicitly. Quality of input does not contribute to the product, because the data shows insufficiency of available facilities, hence requiring the provision of more facilities, and the English teacher should have a good enough background in English education and Ketamansiswaan. The process shows that the English teacher applied “Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani” well but the teacher had missed applying Problem-Based Learning in the 2006 curriculum, which means that the process contributes to the product. The product of the English teaching in implementing “Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani” does not produce satisfactory quality outcomes in the form of students’ participation in English competitions and students cannot speak English fluently, even in class conversations. The researcher concludes that the implementation of “Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani” in English Language Teaching for second grade of SMA Taman Madya Ibu Pawiyatan Yogyakarta still opens to improvement for a better outcome.